ENDOMETRIOSIS AND FERTILITY. KEY MOMENT OF TREATMENT - S. A. Gasparyan; R. M. Ionova; O. S. Popova; A. A. Khripunova (IRBIS LLC, 2016)
Objective. To highlight the modern views on the approaches to the treatment of infertility in endometriosis ovaries. Subject and methods. A review of 30 domestic and foreign sources, on the problem of endometriosis included in the PUBMED and Russian Science Citation Index database. Results. Endometriosis should be treated as a chronic disease that requires long-term development plan for the management of patients in order to maximize the use of drug treatment and elimination of repeated surgical interventions. Using the most gentle tactics of surgical treatment and allow the use of agonists of gonadotropin-releasing hormone preserve ovarian reserve of women of reproductive age and contribute to pregnancy. Conclusion. Given the complexity and controversial nature of many issues related to the etiology, pathogenesis and treatment of endometriosis, it is necessary to develop a unified system concept of a multidisciplinary approach to the tactics of patients with this disease.